Evaluation and management of traumatic conditions in the athlete - Fitch, R. W.; Williams, J. (Clinics in Sports Medicine, 2019)
The athletic training room is filled with a multitude of conditions encompassing many different specialties of medicine. When it comes to traumatic injuries in the training room, many of them are not musculoskeletal in nature. Ultrasound in the training room can help identify serious and subtle solid-organ injury and small pneumothoraces. The discussion of these conditions follows a simple outline that helps identify injury/conditions through a proper history and physical. Evidence-based treatment/management/return to play guidelines are discussed.